(untitled) (International journal of artificial intelligence, 2026)
This article is one of the pressing topics of today, focusing on the content of the study of pedagogical and psychological foundations for the development of independent thinking, a creative person in the process of lifelong education.The focus is on the use of interactive teaching methods that encourage students to think independently.